Continuous carbon nanotube synthesis on charged carbon fibers - Anthony,DB; Sui,X; Kellersztein,I; De,Luca H; White,E; Wagner,HD; Greenhalgh,E; Bismarck,A; Shaffer,M (Composites Part A: Applied Science and Manufacturing, 2018)
Carbon nanotube grafted carbon fibers (CNT-g-CFs) were prepared continuously, spool to spool, via thermal CVD. The application of an in-situ potential difference (300 V), between the fibers and a cylindrical graphite foil counter electrode, enhanced the growth, producing a uniform coverage of carbon nanotubes with diameter ca. 10 nm and length ca. 125 nm. Single fiber tensile tests show that this approach avoids the significant reduction of the underlying carbon fiber strengths, which is usually associated with CVD grafting processes. Single fiber fragmentation tests in epoxy, with in-situ video fragment detection, demonstrated that the CNT-g-CFs have the highest interfacial shear strength reported for such systems (101 ± 5 MPa), comparable to state–of–the–art sizing controls (103 ± 8 MPa). Single fiber pull-out data show similar trends. The short length of the grafted CNTs is particularly attractive for retaining the volume fraction of the primary fibers in composite applications. The results are compared with a short review of the interfacial data available for related systems.